Enhance Ocean Carbon Observations: Successful Implementation of a Novel Autonomous Total Alkalinity Analyzer on a Ship of Opportunity - Seelmann, Katharina; Steinhoff, Tobias; Aßmann, Steffen; Körtzinger, Arne (Frontiers in Marine Science, 2020)
Over recent decades, observations based on merchant vessels (Ships of Opportunity – SOOP) equipped with sensors measuring the CO2 partial pressure (pCO2) in the surface seawater formed the backbone of the global ocean carbon observation system. However, one severe shortcoming of the current SOOP observatory is the fact that it mostly only measures pCO2. Full insight into the marine CO2 system requires the measurement of at least two of the four measurable variables of the marine CO2 system which are pCO2, total alkalinity (TA), dissolved inorganic carbon (DIC) and pH. One workaround is to estimate TA values based on established temperature-salinity parameterizations, but this leads to higher uncertainties and the possibility of regional and/or seasonal biases. Therefore, autonomous SOOP-based TA measurements are of great interest. Our study describes the implementation of a novel autonomous analyzer for seawater TA, the CONTROS HydroFIA TA system (-4H-JENA engineering GmbH, Germany) on a SOOP line operating in the North Atlantic. We present the installation in detail and address major issues encountered with autonomous measurements using this analyzer, e.g. automated cleaning and stabilization routines, and waste handling. Another issue during long term deployments is the provision of reference seawater in large-volume containers for quality assurance measurements and drift correction. Hence, a stable large-volume seawater storage had to be found. We tested several container types with respect to their suitability to store seawater over a time period of 30 days without significant changes in TA. Only a gas sampling bag made of polyvinylidene fluoride (PVDF) satisfied the high stability requirement. In order to prove the performance of the entire setup, we compared the autonomous TA measurements with TA from discrete samples taken during the first two measuring campaigns. Although the measurement accuracy in unattended mode slightly deteriorated compared to our previous system characterization, its overall uncertainty fulfilled requirements for autonomous TA measurements on SOOP lines. A comparison with predicted TA values based on an established and often used parameterization pointed at regional and seasonal limitations of such TA predictions. Consequently, better spatiotemporally covered TA observations are needed, which are now possible with the method described here.